Constraints on possible mechanisms for high-Tc superconductivity - Schürrer, I.; Schachinger, E. (Condensed Matter Physics, 1998)
This paper discusses a phenomenological model used to describe various properties of a dx²−y² superconductor in its temperature as well as frequency dependence, namely, the London penetration depth, the optical conductivity, the microwave conductivity, and the electronic thermal conductivity. We assume the CuO₂ planes to be the dominant feature for superconductivity and develop a 2D-formalism in which inelastic scattering is modelled explicitly by a spectral density which describes a fluctuation spectrum responsible for the superconducting transition and also for the large inelastic scattering observed in the normal state above the critical temperature Tc . The feedback effect of superconductivity on the spectral density is modelled by a temperature dependent low frequency cutoff. Theoretical results are compared with the experimental data and the fact that such a model allows a consistent description of a variety of phenomena is then used to formulate constraints on possible mechanisms of superconductivity in oxides. Дана стаття розглядає феноменологічну модель, що використовується для опису різноманітних властивостей dx²−y²–надпровідників в залежності як від температури, так і від частоти, а саме глибини проникнення Лондона, оптичної провідності, мікрохвильової провідності та електронної термічної провідності. Ми вважаємо, що саме площини CuO₂ є основним чинником для виникнення надпровідності, і тому розвиваємо двомірний формалізм, в якому процеси непружного розсіяння моделюються точно через спектральну густину, що описує флуктуаційний спектр, який є відповідальним за виникнення надпровідного переходу, а також за велике непружне розсіяння, що спостерігається в нормальному стані вище критичної температури Tc . Зворотній вплив надпровідності на спектральну густину моделюється температурнозалежним низькочастотним обрізанням. Теоретичні результати порівнюються з експериментальними даними і, виходячи з того, що дана модель дає змогу зробити послідовний опис цілого ряду явищ, формулюються обмеження на можливі механізми виникнення надпровідності в оксидах.